Use of Optical Coherence Tomography to Demonstrate Retinal Integrity in Division 1 American College Football Players as a Means to Reflect Brain Health With or Without Sports-Related Concussion. - Clark, Joseph F.; Braley, Susan; Mangine, Robert E.; Ellis, James K.; Keuhn-Himmler, Aaron; Hasselfeld, Kim; Mack, Alec A.; Divine, Jon G. (Optometry & Visual Performance, 2021)
Background: The use of baseline evaluations as part of a pre-participation physical for athletic performance is established practice. There is emerging discussion that the creation of reproducible objective measures to document injury or long-term dysfunction resulting from sports-related concussion is needed. This study presents evidence that retinal imaging with optical coherence tomography (OCT) can be used to assess, monitor, and document brain health in college football players. Methods: This is a retrospective chart analysis of 90 University of Cincinnati football players who received OCT imaging (Optovue iVue) of the retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) at least twice during their football careers, including at their exit neurological assessment. RNFL and GCC thicknesses were obtained and are reported in this study. Results: There were no significant changes in RNFL or GCC between the intake and exit exams of enrolled football athletes. RNFL was 104.1±9.1 to 102.8±7.5 microns, and GCC was 97.2±6.3 to 96.1±6.9 microns. There was a similar lack of thickness change documented in 12 subjects before and after sports related TBIs. In one subject who suffered a non-sport related severe TBI, we were able to document greater than 10% change in the RNFL and GCC thicknesses. Conclusions: We conclude that OCT can be used as a means to manage, monitor, and document relative brain health in athletes throughout their sports careers. This objective and quantifiable method can be used as a surrogate to monitor the wellness of athletes participating in sports like football. Other sports medicine practitioners may wish to consider intake and exit measurements as part of a brain health monitoring program for their athletes.